2021
DOI: 10.1002/eat.23516
|View full text |Cite
|
Sign up to set email alerts
|

Gastric symptoms and low perceived maternal warmth are associated with eating disorder symptoms in young adolescent girls

Abstract: Objective This study sought to determine whether gastric symptoms are associated with later eating disorder (ED) symptoms during early adolescence, and whether this relationship is moderated by parental warmth/acceptance and/or the child's sex. Method Longitudinal data from the Adolescent Brain Cognitive DevelopmentSM Study were utilized. Participants ages 9–10 years old (N = 4,950; 2,370 female) completed measures at baseline and 1 year later (Y1). At baseline, gastric symptoms were measured by parent‐reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…DE outcomes were measured using self-report tools with the exception of one study, where parents reported on offspring DE using the Kiddie Schedule for Affective Disorders and Schizophrenia (Kerr et al, 2021). Of the rest, five studies used versions of the Eating Disorder Inventory (EDI-1 and -2) and two implemented the Eating Attitudes Test (EAT-26), with one study using a modified version for children (ChEAT, Meesters et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…DE outcomes were measured using self-report tools with the exception of one study, where parents reported on offspring DE using the Kiddie Schedule for Affective Disorders and Schizophrenia (Kerr et al, 2021). Of the rest, five studies used versions of the Eating Disorder Inventory (EDI-1 and -2) and two implemented the Eating Attitudes Test (EAT-26), with one study using a modified version for children (ChEAT, Meesters et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, unresponsive parenting styles (exhibiting low behavioral monitoring) predicted various DE among daughters, such as body dissatisfaction (Blodgett Salafia et al, 2007) and bulimic behaviors (Krug et al, 2014). However, findings were inconsistent as many studies reported non-significant results for males which were not present for their female counterparts (Krug et al, 2014(Krug et al, , 2016Zubatsky et al, 2015;Kerr et al, 2021). Further, some studies compared longitudinal measurements of parental responsiveness and demandingness using logistic regression analyses (Hautala et al, 2011;Krug et al, 2016).…”
Section: Longitudinal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Culture and Environment working group (CE WG), described previously ( Zucker et al, 2018 ), is responsible for selecting measures and monitoring data pertaining to cultural factors and the social environment. To our knowledge, there are at least 17 published studies to date using CE measures, covering unique associations between family factors (e.g., conflict, monitoring, acceptance/warmth) and amygdala reactivity ( Demidenko et al, 2021 ); suicidality ( Janiri et al, 2020 ), maladaptive guilt ( Donohue et al, 2020 ), eating disorders ( Kerr et al, 2021 ), and early substance exposure ( Wang et al, 2021 ). In addition, school factors and prosocial behavior appear uniquely associated with general psychopathology, accounting for comorbidities across internalizing and externalizing behaviors ( Brislin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%